Hands-on big data analytics with PySpark : analyze large datasets and discover techniques for testing, immunizing, and parallelizing Spark jobs /: analyze large datasets and discover techniques for testing, immunizing, and parallelizing Spark jobs. (2019) - Lai, Rudy; Potaczek, Bartłomiej
No abstract available